2016
DOI: 10.1039/c5ja00470e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the chemical form of different fluorine sources on the formation of AlF molecules in a C2H2/N2O flame

Abstract: The positions for the appearance of AlF molecules in a C2H2/N2O flame and the corresponding sensitivity of the AlF molecular absorbance depend on the bonding state of the used fluorine source HF, H2SiF6, HBF4 and CF3COOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Direct analysis may be particularly beneficial in this field because sample pretreatment is particularly problematic owing to the volatility of many species in which the nonmetals are usually found, and the problems associated with contamination. In fact, the signal obtained for non-metals might be significantly affected by the way in which these are found in the sample, 59 and the way in which such samples are pretreated. This is a challenge when aiming at bulk analysis, but it can be transformed into an advantage to perform some speciation studies.…”
Section: Hr Cs Mas For Determination Of Non-metalsmentioning
confidence: 99%
“…Direct analysis may be particularly beneficial in this field because sample pretreatment is particularly problematic owing to the volatility of many species in which the nonmetals are usually found, and the problems associated with contamination. In fact, the signal obtained for non-metals might be significantly affected by the way in which these are found in the sample, 59 and the way in which such samples are pretreated. This is a challenge when aiming at bulk analysis, but it can be transformed into an advantage to perform some speciation studies.…”
Section: Hr Cs Mas For Determination Of Non-metalsmentioning
confidence: 99%
“…To date, only Acker et al studied the impact of the chemical form of different fluorine sources on the formation of AlF, and found that the AlF molecules are formed by the reaction between the fluorine and aluminum atoms, which are transported into the flame presumably via oxidic and/or carbidic species. 44 Due to significant cost in the development of processors and devices for the gas reaction condition, and great difficulty to identify the elementary processes and to measure the composition of plasma and reaction products, the study of the AlF x vapor phases in microscopic detail or at a molecular level is extremely limited. Major frontiers still exist in formation mechanisms of AlF x complexes over the metal surface during the metal and metal dioxide dry etching process [12][13][14][15]45,46 and some other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The specification of above-mentioned versatile ionic AlF x species leads us to study the possible formation of similar AlF x gaseous phases over the metal surface. To date, only Acker et al studied the impact of the chemical form of different fluorine sources on the formation of AlF, and found that the AlF molecules are formed by the reaction between the fluorine and aluminum atoms, which are transported into the flame presumably via oxidic and/or carbidic species . Due to significant cost in the development of processors and devices for the gas reaction condition, and great difficulty to identify the elementary processes and to measure the composition of plasma and reaction products, the study of the AlF x vapor phases in microscopic detail or at a molecular level is extremely limited.…”
Section: Introductionmentioning
confidence: 99%